Longitudinal Surveillance of Outpatient Tetracycline, Sulfonamide-Trimethoprim and ‘Other’ Antimicrobial Use in Canada, 1995 to 2010 - Shiona K Glass-Kaastra; Rita Finley; Jim Hutchinson; David M Patrick; Karl Weiss; John Conly (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Monitoring the volume and patterns of use of antimicrobial agents is important in light of antimicrobial resistance.